Electrochemical and spectrophotometric methods for polyphenol and ascorbic acid determination in fruit and vegetable extracts - Tulli, Fiorella (Array, 2020)
Research background. Fresh-cut fruits and vegetables are considered sources of antioxidant compounds. However, their shelf life is limited due to nutritional, quality and safety deterioration. Therefore, in recent decades, various methods have been reported for food processing and preservation, as well as for the determination of antioxidant compounds, due to their many benefits when consumed. The aim of the present work is to compare the performance of electrochemical and spectrophotometric methods in the analysis of the content of polyphenolic compounds and ascorbic acid in extracts from fruits (eggplant), edible roots (carrot) and leaves (rocket, lettuce and chard), and evaluate their capability to detect small changes in the antioxidant content in the eggplant extracts previously irradiated with different UV-C light intensities.Experimental approach. Polyphenolic compounds and ascorbic acid were determined by electrochemical and spectrophotometric methods. An enzymatic biosensor and a nanocomposite sensor were used for polyphenolic compounds and ascorbic acid, respectively, in electrochemical measurements, while Folin-Ciocalteu and Kampfenkel methods were used for spectrophotometric measurements.Results and conclusion. Results obtained through the different methodologies were comparable and consistent with each other. Both methods allowed determining the content of ascorbic acid and polyphenolic compounds in the fruit and vegetable extracts. Moreover, both techniques enable the detection of the analyte concentration changes in samples exposed to different UV-C intensities and storage days. Finally, it was observed that the antioxidant capacity depends on the type of food, treatment and storage period.